Impact of eight weeks endurance training on biochemical parameters and obesity-induced oxidative stress in high fat diet-fed rats - Emami, Seyed Reza (J Exerc Nutrition Biochem, 2016)
[PURPOSE]: High-fat diets (HFD) feeding is an important risk factor for obesity that is accompanied with metabolic syndrome. Appropriate exercise is recommended for obesity prevention. The molecular mechanisms and cellular pathways activated in response to HFD and exercise are not well understood. The purpose of this study was to investigate the effect of 8 weeks endurance training on some plasma biochemical parameters and oxidative stress in HFD induced obese rats. [METHODS]: Twenty-eight male Wistar rats were randomly divided into 4 groups: the standard diet (SD) group, endurance training group with a standard diet (ESD), HFD group, and endurance training group with high-fat diet (EHFD). After 8 weeks, blood samples were taken by cardiac puncture and plasma were used for determination of biochemical parameters and oxidative stress biomarkers. [RESULTS]: HFD significantly increased malondialdehyde level and decreased the activities of superoxide dismutase, catalase, and glutathione S-transferase and the content of glutathione in the plasma. HFD also increased activities of aspartate transaminase, alanine transaminase, lactate dehydrogenase, as well as levels of total cholesterol, triglyceride and low-density-lipoprotein-cholesterol. However, endurance training showed protective effect on changes in these parameters. [CONCLUSION]: These findings suggested that HFD alters the oxidant-antioxidant balance, as evidenced by reduction in the antioxidant enzymes activities and glutathione level and enhanced lipid peroxidation. Endurance training can be beneficial for the suppression of obesity-induced oxidative stress in HFD rats through modulating antioxidant defense system and reduces the risk of obesity-associated diseases.